An Electrophoretic Variant of the Human Lactate Dehydrogenase H Subunit - Hattori Sachiko; Yamaguti Kyouko; Urata Mitiyo; Iida Hiroko; Kinosita Sachiko; Hamasaki Naotaka (Japanese Journal of Clinical Chemistry, 2002)
This report describes a patient with an electrophoretic variant of lactate dehydrogenase H subunit. The LDH activity in serum was lower than normal (patient 125 U/L: reference range 261-483 U/L). The LDH isozyme pattern was unique with a broad band spanning the LDH1 to LDH4 regions. We also performed electrophoresis of serum and red blood cell lysate using a discontinuous buffer system. The band 56 patterns obtained were consistent with the existence of an electrophoretic variant of the B locus of Lactate dehydrogenase. By genetic analysis we were able to confirm that the patient is heterozygous for the mutation, causing a substitution of Glutamic acid (GAA) to Lysine (AAA) at codon 230. 血清中のLDH活性が125U/l (基準範囲261～483U/l) と低値を示した患者のアイソザイム分析を行ったところ, 電気泳動像が, LDH 1からLDH 4にかけて陰極側にシフトしたパターンが観察された。さらに患者の赤血球溶血液と血清について, 不連続緩衝液による電気泳動を実施したところH型バリアントであることが確認された。そこでH型アイソザイムをコードするLDH-B遺伝子の解析を行った。その結果, LDH-B遺伝子のコドン230におけるGAA (Glu) からAAA (Lys) へのミスセンス変異ヘテロ接合体であることが判明した。